Uniform Nanowires Containing a Heterogeneousπ‐Conjugated Core of Controlled Length, Composition and Morphology. Issue 33 (13th May 2021) - Nie, Jiucheng; Tao, Daliao; Huang, Xiaoyu; Lu, Guolin; Feng, Chun
Abstract: In this work, it is demonstrated for the first time that heterojunction nanowires, consisting of a gradient and segmented‐like heterogeneous π‐conjugated core with controllable length, composition and morphology, can be generated by co‐self‐seeding of oligo( p ‐phenylene vinylene) (OPV)‐ and oligo( p ‐phenylene ethynylene) (OPE)‐containing block copolymers in spite of different chain lengths and molecular conformation for OPE and OPV. More importantly, based on the understanding of the formation of heterogeneous core by the co‐self‐seeding approach, a "heating/cooling" seeded growth route was developed, by which linear and branched heterojunction nanowires containing a segmented heterogeneous π‐conjugated core of controlled length, composition and morphology can be obtained. This work provides a versatile platform to generate heterojunction nanowires with excellent controllability in length, composition, and morphology. Abstract : Heterojunction nanowires containing a heterogeneous π‐conjugated core of controlled length, composition and morphology were generated by co‐self‐seeding and "heating/cooling"‐seeded growth approaches in spite of distinct molecular size and conformation of π‐conjugated units.